The analysis of torsional shear strength test of sealants for solid oxide fuel cells. Issue 15 (15th October 2017) - Fakouri Hasanabadi, M.; Faghihi-Sani, M.A.; Kokabi, A.H.; Malzbender, J.
Abstract: A torsion test recently implemented for solid oxide fuel cell sealant materials is analyzed as a method for measuring the shear strength of sealant for solid oxide fuel cells. The finite element method is used to simulate the stress distribution in the hourglass-shaped steel specimens with intermediate sealant layer with different specimen's dimensions and configurations. Also, it is analyzed how stress concentration changes if the sealant does not completely fill the gap or is squeezed out of gap. The reduction of seal thickness to outer radius ratio results in an increase in stress concentration at the outer edge of sealant. The developed specimens with a hollow halve steel plate as well as the ones with two hollow halve steel plates appear to be suitable choices for torsional shear strength test, reducing the torque for fracture and stress concentrations. Effects of lack of filling and squeezing out of gap onto the stress distribution are negligible compared to the effect of pre-existing discontinuities.